MINIMISASI BIAYA PRODUKSI KEDELAI DI KABUPATEN LOMBOK TENGAH - I DEWA GEDE SUARTHA; MADE SUMA WEDASTRA (Universitas Mahasaraswati K. Mataram, 2023)
Generally, farmers plant soybeans after harvesting rice, which are cultivated using a tugal and spread system. The cost and production of soybeans produced with these two cropping systems will differ from one another. Under these conditions, how much production must be produced so that the production costs of cultivating soybeans in Central Lombok Regency are minimum?Based on these problems, this research wants to know the amount of soybean production that must be achieved by farmers in Central Lombok Regency, so that production costs are minimal. Using 60 respondents who were determined by purposive disproportionate random sampling in two sub-districts on the basis of the two sub-districts being used as soybean production centers, namely Jonggat and Praya Barat sub-districts, each 30 people.The results of inferential analysis of the cubed polynomial cost function model obtained the cost function equation: TC = 3,641.71 + 711.23Y + 0.28Y² - 0.000093Y³, with a coefficient of determination (R²) = 73.00%, meaning 73.00% variation the value of the total cost is determined by soybean production and only 22.00% of the total cost is influenced by factors outside production. On the other hand, the amount of soybean production that must be produced by farmers so that the minimum production costs are 3,010.75 kg with a minimum cost of Rp. 2,144,979.70 or by increasing the cultivated soybean area from 44.52 acres to 237.06 acres.